2015
DOI: 10.1002/ajmg.a.36882
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of the 20q11.2 microdeletion syndrome: Six new patients

Abstract: Interstitial microdeletions of 20q chromosome are rare, only 17 patients have been reported in the literature to date. Among them, only six carried a proximal 20q11.21-q11.23 deletion, with a size ranging from 2.6 to 6.8 Mb. The existence of a 20q11.2 microdeletion syndrome has been proposed, based on five previously reported cases that displayed anomalies of the extremities, intellectual disability, feeding difficulties, craniofacial dysmorphism and variable malformations. To further characterize this syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…Mutations and deletions of SAMHD1 have been associated with systemic lupus erythematosus, and recently homozygous mutations in SAMHD1 were found in 8.3% of Jedraszak et al, 2015Callier et al, 2006Iqbal et al, 2007Hiraki et al, 2011Gervasini et al, 2013Posmyk et al, 2014 Total reported patients Our case (DECIPHER…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Mutations and deletions of SAMHD1 have been associated with systemic lupus erythematosus, and recently homozygous mutations in SAMHD1 were found in 8.3% of Jedraszak et al, 2015Callier et al, 2006Iqbal et al, 2007Hiraki et al, 2011Gervasini et al, 2013Posmyk et al, 2014 Total reported patients Our case (DECIPHER…”
Section: Discussionmentioning
confidence: 75%
“…Recently, a new contiguous gene disorder was described, characterized by a 89 distinct phenotype of intellectual disability, feeding difficulties, craniofacial dysmorphisms, and anomalies of the extremities [Jedraszak et al, 2015]. The SRO in these patients was defined by a 1.6-Mb deletion [Jedraszak et al, 2015] involving several RefSeq sequences, including the 3 OMIM disease-causing genes GDF5 ( * 601146), EPB41L1 ( * 602879), and SAMHD1 ( * 606754).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations